Prevalence of hypodontia in Chinese orthodontic patients - Pambudi Rahardjo (Dental Journal (Majalah Kedokteran Gigi), 2006)
Hypodontia is a phenomenon of congenitally missing teeth in human. A thousand and twelve panoramic radiographs of Chinese orthodontic patients were examined for agenesis of permanent teeth including third molars. The patients with missing teeth were divided into four group: the patients with missing less than 4 molars, missing all third molars, hypodontia and oligodontia. The result revealed, 210 patients affected one or more teeth agenesis with a total of 455 teeth missing. The prevalence of tooth agenesis was maxillary third molar 259 (56.9%), mandibular third molar 143 (31.4%), mandibular second premolar 15 (3.3%), mandibular lateral incisors 13 (2.8%), maxillary lateral incisors 8 (1.7%), maxillary second premolars 7 (1.5%), other teeth 10 (2.2%) respectively. Of the mesial mandibular first permanent molar, mandibular second premolars were the most frequent missing teeth. Although hypodontia did not represent a public health problem, from orthodontic point of view it might cause esthetic and masticatory function disorders as well as more complex mechanotherapy of a patient.